The Effectiveness of Remote Motivation for Creative Work – Results of Experimental Research - Lipka, Anna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: The article presents the results of experimental research on the influence of various levels of motivational synergy (the combination of external and internal motivation) on the effectiveness of motivating people to do creative work under time pressure and in remote conditions.Research Design & Methods: The study used a pre-experimental, static group scheme covering 107 people. Three hypotheses on various degrees of the motivational synergy were verified for the criteria of evaluating the products of creative work. The criteria included originality, fluidity, and ideational flexibility.Findings: The research shows that, when fully using motivational synergy, remote motivation has a bigger impact on ideational fluidity than when it does not.Implications / Recommendations: The conclusions of the research assess the impact of full and incomplete motivational synergy in remote conditions on ideational fluidity and the diversity of the effects of creative work.Contribution: The article contributes to the research on motivational synergy as it pertains to creative work, in remote conditions, using an experiment. Thus, it goes beyond the exclusive opposition of external and internal motivation for this type of work, referring to modules of experience. This is the novel contribution of the work. The results can be used to program processes for developing, appraising, and remunerating employees.